Physical and virtual learning spaces in higher education : concepts for the modern learning environment - Keppell, Mike, 1961-; Souter, Kay, 1952-; Riddle, Matthew, 1969- (Hershey, Pa. : Information Science Reference, 2012)
'This book documents real-world experiences of innovators in higher education who have redesigned spaces for learning and teaching, including physical, virtual, formal, informal, blended, flexible, and time sensitive factors' --Provided by publisher.
Includes bibliographical references (p. 295-322) and index.
Keywords: College environment; Classroom environment; Virtual reality in higher education; Blended learning